2017
DOI: 10.1039/c7dt00383h
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin functionalized radioactive gold nanoparticles (MGF-198AuNPs) in prostate tumor therapy: green nanotechnology for production, in vivo tumor retention and evaluation of therapeutic efficacy

Abstract: We report here an innovative feature of green nanotechnology-focused work showing that mangiferin-a glucose functionalized xanthonoid, found in abundance in mango peels-serves dual roles of chemical reduction and in situ encapsulation, to produce gold nanoparticles with optimum in vivo stability and tumor specific characteristics. The interaction of mangiferin with a Au-198 gold precursor affords MGF-AuNPs as the beta emissions of Au-198 provide unique advantages for tumor therapy while gamma rays are used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 63 publications
5
62
0
5
Order By: Relevance
“…Chemical methods utilize chemicals and solvents, like sodium borohydride (NaBH4), hydrazine and citrate to initiate the synthetic process and promote nanoparticle nucleation. It has been demonstrated that the most efficient reducing agents are NaBH4 and hydrazine, but these agents present the disadvantage that are biologically and environmentally toxic [20][21][22][23]. Suchomel P. and co-workers prepared AuNPsby the reduction of tetrachloroauric acid using maltose in the presence of nonionic surfactant Tween 80 at various concentrations, in order to control the size of the resulting AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical methods utilize chemicals and solvents, like sodium borohydride (NaBH4), hydrazine and citrate to initiate the synthetic process and promote nanoparticle nucleation. It has been demonstrated that the most efficient reducing agents are NaBH4 and hydrazine, but these agents present the disadvantage that are biologically and environmentally toxic [20][21][22][23]. Suchomel P. and co-workers prepared AuNPsby the reduction of tetrachloroauric acid using maltose in the presence of nonionic surfactant Tween 80 at various concentrations, in order to control the size of the resulting AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium borohydride is commonly used as a reducing agent in the synthesis of AuNPs; however, it is an environmental contaminant and highly toxic to biological systems [33]. Therefore, phytochemicals like epigallocatechin [34] and mangiferin [35] have been utilized for the green synthesis of AuNPs. The reducing agent used in this study was the pomegranate peel extract (PPE) to synthesize AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Mango peel contains a large abundance of mangiferin (42% of the total polyphenols, Figure 5)a heat stable and naturally occurring pharmacologically active phytochemical with antiinflammatory, antitumor and antioxidant activities. 27,[58][59][60] As shown in Figure 5 As shown in Figures 1, 2 and 5, the antioxidant power of mangiferin and other phytochemicals in mango peel are responsible in transforming gold salt into the corresponding AuNPs.…”
Section: Drug Loading Of Phytochemicals From Mango Peel On Gold Nanopmentioning
confidence: 93%
“…In order to understand the extent of loading of mangiferin onto AuNPs, which we refer as drug loading, we have performed key experiments as elaborated in numerous publications on green nanotechnology from our laboratory. [19][20][21]23,26,27,35,61 We hypothesized that the corona around gold nanoparticles in MP-AuNPs comprises of mostly the encapsulation of mangiferin due to the large abundance of this phytochemical in the mango peel ( Figure 5). Validating this hypothesis is significant in understanding drug loading of mangiferin around gold nanoparticles.…”
Section: Drug Loading Of Phytochemicals From Mango Peel On Gold Nanopmentioning
confidence: 99%